Bilateral Adrenal Hemorrhage and Adrenal Insufficiency in the Context of Polycythemia Vera: A Case Report and Review of the Literature - Sara Soltanmohammadi; Mehrbod Vakhshoori; Ghazaleh Sajadi; Maryam Heidarpour (Case Reports in Medicine)
Background. Polycythemia vera (PV) is a myeloproliferative disorder presented with different manifestations. However, bilateral adrenal hemorrhage (BAH) and adrenal insufficiency (AI) are rare manifestations. Herein, we described a patient who suffered from BAH and AI in the context of PV. Case Presentation. A 60-year-old man with an underlying history of PV was admitted with severe abdominal pain, nausea, and loss of consciousness. Primitive computed tomography (CT) scan findings revealed bilateral adrenal masses (right: 40 ∗ 23 mm, left: 60 ∗ 35 mm) with the second scan showing quite similar results (right adrenal: 40 ∗ 29 mm, left adrenal: 48 ∗ 26 mm) suggesting BAH. The further adrenal assessment proved concurrent AI. Both adrenal masses resolved completely after 15 months. However, the patient still suffered from AI. Conclusion. BAH and AI in patients with PV should be considered rare complications requiring high clinical suspicion for early diagnosis and treatment to avoid life-threatening outcomes.